Characterization and Modelling of LeBlanc Hydrodynamic Stabilizer: A Novel Approach for Steady and Transient State Models. (11th June 2015) - Cunico, Marlon Wesley Machado
Abstract : As result of increase of customers' demands, products become more complexes and dynamics control increased its role into product development. As example, clothing washing machines use LeBlanc balancers in order to reduce vibration issues. Nevertheless, the behaviour of such apparatus is still hard to describe and the numerical simulation of this sort of vibration control is based on ball rings. The main goal of this work is to define and characterize a numerical model that describes the hydrodynamics balance ring in the transient state in addition to steady state models. As consequence, the behaviour of balance ring was identified in a computational fluid dynamics tool and an equation that describes restoration forces, unbalance, force phase, and eccentricity was found.